THE ASSOCIATION BETWEEN OBJECTIVE MEASURES OF INTERMITTENT SEDENTARY BREAKS WITH RECURRENT FALL RISK IN OLDER MEN. (20th December 2022) - Roe, Lauren; Harrison, Stephanie; Cawthon, Peggy; Ensrud, Kristine; Gabriel, Kelley; Kado, Deborah; Cauley, Jane
Abstract: BACKGROUND: We assessed the relationship between objectively measured sedentary bout frequency with recurrent falls (2+ falls/year). METHODS: The sample included 2, 918 men aged 79.0±5.1 years attending the Osteoporotic Fractures in Men Study (MrOS) Year 7 (2007-2009) visit. Sedentary bout frequencies were defined as the average daily number of transitions out of 5+ minutes sedentary (<1.5 METS). Falls were self-reported from mailed questionnaires. Generalized Estimating Equations estimated the odds of recurrent falls. RESULTS: Over four follow-up years, 1, 025 (35.1%) men had recurrent falls. Compared to men with <13.6 transitions from sedentary (Quartile (Q)1), the odds of recurrent falls among men with 13.6-<17.0 transitions (Q2), 17.0-<20.4 transitions (Q3), and 20.4-<34.6 transitions (Q4) were 0.82 (95%CI: 0.66-1.01), 0.79 (95%CI: 0.64, 0.99), and 1.01 (95%CI: 0.81, 1.27), respectively, after adjustment. CONCLUSIONS: A U-shaped association may exist between sedentary bout frequency and recurrent falls risk. The least and most active men are at higher risk.